Bed load transport and boundary roughness changes as competing causes of hysteresis in the relationship between river discharge and seismic amplitude recorded near a steep mountain stream. Issue 5 (26th May 2017) - Roth, Danica L.; Finnegan, Noah J.; Brodsky, Emily E.; Rickenmann, Dieter; Turowski, Jens M.; Badoux, Alexandre; Gimbert, Florent
Abstract: Hysteresis in the relationship between bed load transport and river stage is a well‐documented phenomenon with multiple known causes. Consequently, numerous studies have interpreted hysteresis in the relationship between seismic ground motion near rivers and some measure of flow strength (i.e., discharge or stage) as the signature of bed load transport. Here we test this hypothesis in the Erlenbach stream (Swiss Prealps) using a metric to quantitatively compare hysteresis in seismic data with hysteresis recorded by geophones attached beneath steel plates within the streambed, a well‐calibrated proxy for direct sediment transport measurements. We find that while both the geophones and seismometers demonstrate hysteresis, the magnitude and direction of hysteresis are not significantly correlated between these data, indicating that the seismic signal at this site is primarily reflecting hysteresis in processes other than sediment transport. Seismic hysteresis also does not correlate significantly with the magnitude of sediment transport recorded by the geophones, contrary to previous studies' assumptions. We suggest that hydrologic sources and changes in water turbulence, for instance due to evolving boundary conditions at the bed, rather than changes in sediment transport rates, may sometimes contribute to or even dominate the hysteresis observed in seismic amplitudes near steep mountain rivers. Plain Language Summary: An increasing number of studies have recently observed changes in the amount of seismic shaking (hysteresis) recorded near a river at a given discharge during floods. Most studies have assumed that this hysteresis was caused by changes in the amount of sediment being transported in the river and have therefore used the hysteresis to assess sediment transport rates and patterns. We examine concurrent seismic and sediment transport data from a steep mountain stream in the Swiss Prealps and find that changes in seismic shaking are unrelated and even opposed (increasing versus decreasing) to changes in sediment transport rates for four out of five transport events. Water turbulence, rather than sediment transport, appears to be the strongest source of seismic shaking, and changes in seismic shaking are most likely caused by changes in turbulence or how turbulence transmits energy through the river bed. These effects may be due to rearrangement of sediment around large boulders on the bed or slight shifting of the boulders themselves. Our results have significant implications for the growing field of fluvial seismology and the evaluation of seismic data near rivers, as previous interpretations of seismic hysteresis as evidence for sediment transport may not always be accurate. Key Points: Hysteresis in seismic signals near rivers may not always indicate hysteresis in bed load sediment transport rates, as previously assumed The seismic signal generated by water turbulence, rather than sediment transport, can dominate seismic observations near rivers Shifting of grains on the river bed may change the seismic response to fluid flow between rising and falling water levels (hysteresis)